2020
DOI: 10.1177/2396941519899311
|View full text |Cite
|
Sign up to set email alerts
|

The word learning profile of adults with developmental language disorder

Abstract: Background and aims Previous investigations of word learning problems among people with developmental language disorder suggest that encoding, not retention, is the primary deficit. We aimed to replicate this finding; test the prediction that word form, not the linking of form to referent, is particularly problematic; and determine whether women with developmental language disorder are better word learners than men with developmental language disorder. Methods Twenty adults with developmental language disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 65 publications
6
48
0
Order By: Relevance
“…Even if this were true, we have no indication from the data that any reduction in recall would be greater in the children with DLD. A recent study by McGregor et al [ 34 ] is informative in this regard. Those investigators studied adults with DLD and found retention at 1 month to be comparable to that of their typical language peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if this were true, we have no indication from the data that any reduction in recall would be greater in the children with DLD. A recent study by McGregor et al [ 34 ] is informative in this regard. Those investigators studied adults with DLD and found retention at 1 month to be comparable to that of their typical language peers.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks in part to the recent resurgence in retrievalbased research, several researchers have begun to explore the role that retrieval might play in the word learning of children and young adults with DLD [33][34][35]. The McGregor et al study [35] included comparisons between retrieval and no-retrieval learning conditions.…”
Section: Retrieval and Word Learning In Individuals With Dldmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated male-to-female prevalence ratio within the DLD population is 1.3:1 ( Tomblin et al, 1997 ), whereas the male-to-female receipt-of-services ratio is 1.71:1 in the United States ( Morgan et al, 2017 ) and 2.55:1 in the United Kingdom ( Lindsay & Strand, 2016 ). Girls and boys may present with different profiles of strengths and weaknesses in language itself ( McGregor et al, 2020 ) or differences in social behavior that serve to magnify (in the case of boys) or hide (in the case of girls) their language weaknesses ( Hart et al, 2004 ; Toseeb et al, 2017 ).…”
Section: Children With Dld Are Underservedmentioning
confidence: 99%
“…The larger representation of boys could be fair because community samples do reveal a higher prevalence of DLD among boys than girls; however, the difference is small and not always significant (Norbury et al, 2016). • Girls and boys may present with different profiles of strengths and weaknesses in language itself (McGregor et al, 2020) or differences in social behavior that serve to magnify (in the case of boys) or hide (in the case of girls) their language weaknesses (Hart et al, 2004;Toseeb et al, 2017).…”
Section: Inequities Related To Gendermentioning
confidence: 99%